Exploration of Sensory Processing Difficulties among Children Attending Primary School in Denmark - Ann Natasja Nielsen; Åse Brandt; Karen la Cour (Hindawi-Wiley, 2021)
Current research shows that children with sensory processing (SP) difficulties have limited participation and enjoyment in their daily activities at school. The aim of this study was to explore the prevalence of SP difficulties among Danish children and to explore possible associated factors. Since SP difficulties can affect children's prerequisites for participation in school activities and learning possibilities, this study focused on primary school children. Method. The study was designed as a cross-sectional survey. The sample consisted of 1723 children age 5 to 11 years, who were attending Danish public school (45.5% girls, 53.2% boys). The parents or caregivers of the child completed a Short Sensory Profile (SSP) questionnaire and a demographic questionnaire. One-way ANOVA was used to examine differences between girls and boys regarding sports, geographic area, and parental level of education. Chi-square analysis was used to explore the relationship between sex and SPP scores in the different behavioral sections. Logistic regression analysis was used to investigate possible associations between SP difficulties and sex and the included demographics. Results. A total of 21.3% of the children had SSP scores suggesting SP difficulties. Boys had a higher probability of having SP difficulties than girls (odds ratio OR=1.55, confidence level (Cl): 1.22, 1.97). An association was found between participating in sports outside of school and SP difficulties (OR=0.55, Cl: 0.47, 0.65 (p≤0.001)). Additionally, a slight association between SP difficulties and parental education level (OR=0.80) was found. No association was found regarding geographic area, i.e., where in Denmark the children attended school (OR=1.00). Conclusion. The study results suggest that approximately 20% of the children in Danish public schools might have SP difficulties and over 20% might be at risk of having SP difficulties. The results suggest that Danish schools should focus on both identifying children with SP difficulties and implement interventions such as sensory integration through occupational therapy to help children with SP difficulties, in order to improve their ability to participate and learn from school activities.